OPTICAL DENSITY OF YELLOW PRINTS AT COATED AND UNCOATED PAPER - Gema Sukmawati Suryadi; Susiani Susiani; Mawan Nugraha; Balqis Azhar Ulfah Alifah; Meuthia Suryani (Politeknik Negeri Media Kreatif, 2019)
Optical Density is one of the important parameters used to control print quality. Optical density in print materials is form of interaction of ink with paper. This research is oriented to the investigation of optical density value of Yellow printing ink on coated and uncoated paper. The main purpose of this study is to analyze the effect of printing ink thickness on optimal density value. The optical density value of yellow prints obtained using densitometer measurement, printed using IGT method on coated and uncoated paper. Ink thickness variations are applied (0.8 - 9.6 Î¼m). Density values was found to increase as the ink layer thickness increased to a certain point called the optimal density (2.4 Î¼m ink thickness on coated paper and 4.5 Î¼m on uncoated paper). Optical density of yellow printing ink on coated paper is higher uncoated paper, which relates to porosity on paper